Potential Modulatory Role of Phoenixin-14 in Epithelial–Mesenchymal Transition of Endometriotic 12Z Cells - Karolina Iwona Kulinska; Magdalena Wierzbicka; Anna Dera-Szymanowska; Krzysztof Szymanowski; Mirosław Andrusiewicz; Maria Wołuń-Cholewa (Biomedicines)
Background/Objectives: Endometriosis is a painful chronic condition in which the endometrium grows outside the uterus. The epithelial–mesenchymal transition (EMT) is critical to endometriosis progression, where cells lose epithelial traits and gain invasiveness. Methods: This study investigates the effects of phoenixin-14 (PNX-14), a neuropeptide found at reduced levels in endometriosis patients, on the expression of two molecular EMT markers, CDH1 (E-cadherin) and THBS2 (thrombospondin 2), as well as cell viability in the endometriosis-derived 12Z cell line. Cells were treated with physiological (0.2 nM) and endometriosis-relevant (0.05 nM) concentrations of PNX-14. Gene expression was analyzed using RT-qPCR, while protein localization was assessed by immunocytochemistry. Cell viability was measured using an XTT assay. Results: THBS2 gene expression was significantly decreased, and CDH1 remained unchanged in cells stimulated by 0.05 nM PNX-14. Immunolocalization indicates a weaker THBS2 and CDH1 protein immunosignal reaction for 0.05 nM PNX-14. PNX-14 treatment also exhibited a biphasic effect on cell viability. Lower concentration initially decreased viability at 48 h but then significantly increased it at 72 h. This increase coincided with the decrease in THBS2 expression, suggesting a potential link between PNX-14, THBS2, and cell viability. Conclusions: A negative correlation between cell viability and the expression of both EMT markers further highlights their possible involvement in the survival and adaptability of ectopic epithelial cells. Our findings suggest a complex interplay between PNX-14, EMT markers, and cell viability in ectopic epithelial cells. PNX-14’s ability to modulate these factors warrants further investigation to elucidate its role in endometriosis.